The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2131/jts.31.149
|View full text |Cite
|
Sign up to set email alerts
|

QUANTITATIVE MEASUREMENT OF SPLICED XBP1 mRNA AS AN INDICATOR OF ENDOPLASMIC RETICULUM STRESS

Abstract: The unfolded protein response (UPR) events triggered by the accumulation of unfolded protein in endoplasmic reticulum (ER) activate the three UPR signaling pathways mediated by IRE1, ATF6 and PERK. Spliced XBP1 mRNA induced by activated IRE1 is translated to the protein, a potent transcription factor that induces BiP expression. XBP1 is also induced by activated ATF6. It is thus thought to be an important marker reflecting both IRE1 and ATF6 signaling in response to ER stress. For quantitative measurement of X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(102 citation statements)
references
References 21 publications
3
99
0
Order By: Relevance
“…6B). Figure 6C shows that treatment with palmitate alone or mixed with oleate/linoleate induced partial but significant XBP-1 mRNA splicing, further evidence of increased ER stress (22). As a positive control, we showed that thapsigargin, a chemical inducer for ER stress, induced a greater increase of CHOP and GRP78 mRNA (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…6B). Figure 6C shows that treatment with palmitate alone or mixed with oleate/linoleate induced partial but significant XBP-1 mRNA splicing, further evidence of increased ER stress (22). As a positive control, we showed that thapsigargin, a chemical inducer for ER stress, induced a greater increase of CHOP and GRP78 mRNA (Fig.…”
Section: Resultsmentioning
confidence: 59%
“…6). Activation of IRE1 induces the cleavage of the XBP1 mRNA, generating a spliced mRNA, which encodes a potent novel transcriptional activator of downstream unfolded protein response target genes (7)(8)(9)(10)13). This spliced mRNA can rapidly be detected by semiquantitative PCR, allowing the identification of activated unfolded protein response.…”
Section: Discussionmentioning
confidence: 99%
“…The presence in this 26-nucleotide fragment of a PstI restriction site further allowed us to distinguish between both XBP1 forms by restriction analysis of PCR-amplified complementary DNA, and thus to assay for ER stress response activation (Hirota et al, 2006). By reverse transcriptase-PCR we found the induction of sXBP1 mRNA following treatment of BxPC-3 cells with 20 mM edelfosine ( Figure 2f).…”
Section: Edelfosine Induces Sxbp1 Expressionmentioning
confidence: 93%